Tværvidenskabelig spørgeskemakonstruktion (Sociologisk Forskning, 2005)
Focussing on construction of questionnaires, the author is answering the following question: H ow are respondents solving semantic and other cognitive tasks, and what are the resulting consequences with regard to questionnaire construction? The article — also comprising research grounded questionnaire construction recommendations developed by the author — is based on textual analysis of a wide range of English quantitative methodology literature problematizing questionnaire construction as arts and crafts striving to convert questionnaire construction into an interdisciplinary science comprising linguistics and cognitive psychology. The author is arguing that respondents, when solving their tasks, should be offered wide-ranging semantic and other cognitive reliefs based on survey researcher's thorough linguistic and psychological expertise.